MULTICULTURAL ISLAMIC RELIGIOUS EDUCATION LEARNING - Sufinatin Aisida (Universitas Islam Malang, 2022)
This study discusses the learning of multicultural Islamic religious education at SMA Antartika Sidoarjo and SMA NU 1 Gresik, East Java. The research approach is qualitative, the type of research is a case study. The results showed that the learning components contained the values of multicultural Islamic education in Antarctica Sidoarjo High School and NU 1 Gresik High School, namely: teachers, students, objectives, materials, methods, media/sources, environment. The learning process is carried out by appreciating and accommodating the diversity of both the learning of Islamic Religious Education subjects as well as the learning of multicultural values, and school achievement. Multicultural Islamic Religious Education Learning Model in Antarctica Sidoarjo High School and NU 1 Gresik High School, which integrates all learning components based on multicultural Islamic values, with a scientific approach, in Antarctica High School found a learning model using a concept map approachKeywords:Ã‚Â Learning, Islamic Religious Education, Multicultural, High School